تعسّف الصحفي في استعمال حقّ النشر - بوساحة, نجاة (جامعة الوادي University of Eloued, 2013)
إساءة استعمال حق النشر من قبل الصحفي بقصد إضرار الغير، تتجسد عندما يحيد الصحفي بهذا الحق عن الحدود التي رسمها له القانون، و بصفة خاصة إذا اقترن استعماله بسوء نية أو بقصد الإضرار، أو تبين أن ثمة عوامل شخصية دفعت إليه، و عليه فإساءة استعمال حق النشر تعتبر محققة متى كان هناك مساس بمصلحة عامة أو خاصة ما يستوجب المساءلة المدنية. Summary: The abuse of the right of publishing from the journalist With a view to harm others. This appears when the journalist comes out of this right from the border drawn by his law; specially if combined use in bad faith, if intent to damage, or show that there are personal factors pushed him. So the copyright abuse is considered realized when there is prejudice to the public or private interest which requires civil accountability
Keywords: التعسّف؛ الصّحفي؛ حقّ النشر؛ الإعلام؛ الحريّة الصحفيّة؛ الجمهور